163k views
3 votes
How do I solve: (-3/8x) + (1/6) = (-7/12)

User Bernadine
by
4.7k points

1 Answer

6 votes

Solution

Step 1

Write the equation


(-3)/(8)x\text{ + }(1)/(6)\text{ = }(-7)/(12)

Step 2


\begin{gathered} Subtract\text{ }(1)/(6)\text{ from both sides} \\ \\ (-3)/(8)x+(1)/(6)-(1)/(6)=(-7)/(12)-(1)/(6) \\ \\ (-3)/(8)x\text{ = }(-9)/(12) \end{gathered}

Step 3

Multiply each term by the Lcm of 8 and 12 = 24


\begin{gathered} (-3)/(8)x\text{ }*\text{ 24 = }(-9)/(12)*24 \\ \\ -9x\text{ = -18} \\ \\ x\text{ = }(-18)/(-9) \\ \\ x\text{ = 2} \end{gathered}

Final answer

x = 2

User Selfboot
by
5.1k points